Anthropogenic and genetic conditions for phosphate mobility in individual structural fractions of Podzolized chernozem - Tsvyk, Tatiana; Tsvyk, Tatiana (Springer Nature, 2021)
The genetic and anthropogenic conditions for the formation of indicators of phosphate regime of podzolized chernozem are analyzed. The silt content in separate structural fractions of the soil under study is examined and the dependence of the formation of the structural state on the content of the silt fraction and the method of use is determined. The nature of the change in the degree of phosphate mobility, depending on the agronomically valuable structure, as one of the main indicators of the availability of phosphorus to plants is evaluated. The content of mobile phosphorus in separate structural fractions was monitored and its redistribution was characterized depending on the content of silt fraction. The parameters of soil buffer capacity with respect to phosphorus are established as a property of the soil to maintain the phosphorus concentration at a constant level.
Keywords: mobile phosphorus, degree of mobility of phosphates, structural fractions, podzolized chernozem, silt content.